Gut Microbiota in Multiple Sclerosis: Possible Influence of Immunomodulators - Cantarel, Brandi L.; Waubant, Emmanuelle; Chehoud, Christel; Kuczynski, Justin; DeSantis, Todd Z.; Warrington, Janet; Venkatesan, Arun; Fraser, Claire M.; Mowry, Ellen M. (Journal of investigative medicine, 2015)
Objectives Differences in gut bacteria have been described in several autoimmune disorders. In this exploratory pilot study, we compared gut bacteria in patients with multiple sclerosis and healthy controls and evaluated the influence of glatiramer acetate and vitamin D treatment on the microbiota. Methods Subjects were otherwise healthy white women with or without relapsing-remitting multiple sclerosis who were vitamin D insufficient. Patients with multiple sclerosis were untreated or were receiving glatiramer acetate. Subjects collected stool at baseline and after 90 days of vitamin D3 (5000 IU/d) supplementation. The abundance of operational taxonomic units was evaluated by hybridization of 16S rRNA to a DNA microarray. Results While there was overlap of gut bacterial communities, the abundance of some operational taxonomic units, including Faecalibacterium, was lower in patients with multiple sclerosis. Glatiramer acetate–treated patients with multiple sclerosis showed differences in community composition compared with untreated subjects, including Bacteroidaceae, Faecalibacterium, Ruminococcus, Lactobacillaceae, Clostridium, and other Clostridiales. Compared with the other groups, untreated patients with multiple sclerosis had an increase in the Akkermansia, Faecalibacterium, and Coprococcus genera after vitamin D supplementation. Conclusions While overall bacterial communities were similar, specific operational taxonomic units differed between healthy controls and patients with multiple sclerosis. Glatiramer acetate and vitamin D supplementation were associated with differences or changes in the microbiota. This study was exploratory, and larger studies are needed to confirm these preliminary results.